Integration of Multiple Health Disciplines the Role of Public Health, Nutrition, Pharmacy, Nursing and Health Administration in Enhancing Healthcare Quality: A Systematic Review - Ghazwani, Ali Sulaiman Hassan; Alkhudhayr, Omar Abdullah Othman; Salem Alqarna, Mohammed Hamdan; Alghamdi, Mohammed Saeed Khader; Aldawsari, Nasser Mesfer Musaad; Y Alharbi, Naief Ghazi; Naif Alshahrani, Shalan Mohammed; Ebrahim Alssab, Abdullah (Journal of Neonatal Surgery, 2025)
Background: Healthcare systems today are undergoing fast transformation worldwide from fragmented, acute-cure and illness based systems to integrated, holistic and patient centered care. This present study tries to evaluate the multiple health disciplines and the role of public health, nutrition, pharmacy, nursing, and health administration in enhancing healthcare quality. Study Objectives: The main objective of this systematic review is to systematically review and summarize evidence of the role of public health, nutrition, pharmacy, nursing, and health leadership in the healthcare system in Saudi Arabia and its combined impact on health care quality. Materials and Methods: The study type or the research design selected was exploratory research design. The researcher had screened various studies conducted in the area of health care integration, including the above mentioned areas. Researcher will evaluate the studies based on administrative practices for the cause of integration, the policy framework of government, challenges and related issues along with the measures taken for the same. The respective timeline of the study was from the period of 2014 to 2024. Results: Issues in policy alignment, regional equity, and longitudinal evaluation are still barriers to fully realizing integrated health services. The progression of interdisciplinary frameworks and collaborative building will support key enablers for delivering quality, patient-centered care throughout the Kingdom.